Novel 3D-printed buoyant structures for improvement in flue gas CO2-derived microalgal biomass production by enhancing anti-biofouling on vertical polymeric photobioreactor. (15th September 2022) - Sung, Young Joon; Yoon, Hong Ki; Lee, Jeong Seop; Joun, Jaemin; Yu, Byung Sun; Sirohi, Ranjna; Sim, Sang Jun
Abstract: Novel 3D-printed buoyant structures can be applied in various environmental processes because of their considerable advantages. Microalgae cultivation in photobioreactors, directly supplemented by industrial CO2, enables environmental pollution mitigation/cleanup and sustainable energy production. However, in photobioreactor systems, biofilm formation due to gas bubbling decreases microalgal productivity. Therefore, in this study, we aimed to develop a novel 3D-printed buoyant structure to suppress biofilm formation. The 10 mm-sized spherical buoyant structure reduced the height and area of the biofilm by 58.3% and 82.5%, respectively. The structure decreased space where bubble burst occurred and controlled the bubble size, reducing the overall biomass loss by 58.7%. It did not reduce photobioreactor performance noticeably during semi-continuous cultivation, indicating the possibility of long-term applicability. In large-scale outdoor microalgae cultivation using flue gas CO2, the buoyant structure improved the cell density and biodiesel production potential without contamination. This study provides a promising strategy to contribute to biological CO2 mitigation through the utilization of flue gas CO2 for enhanced microalgal production, paving the way for energy and environmental sustainability. Graphical abstract: Image 1 Highlights: 3D-printed buoyant structure prevented biofouling in a polymeric photobioreactor. The 10 mm-sized spherical structure decreased the height and area of the biofilm. Buoyant structure prevented bursting of bubbles and generation of large bubbles. Biofouling was controlled in semi-continuous culture without structure replacement. Biofouling suppression contributed to microalgal valorization of flue gas CO2 .